COVID-19 and chronic obstructive pulmonary disease: what is known about the unknown - E. S. Ovsyannikov; S. N. Avdeev; A. V. Budnevskiy; E. S. Drobysheva; A. Ya. Kravchenko (Туберкулез и болезни лёгких)
The article reviews 60 publications and addresses key aspects of concurrent COVID-19 and chronic obstructive pulmonary disease (COPD). It presents data stating that COPD patients have higher expression of the receptor of angiotensin-converting enzyme 2 in the lungs and this may contribute to a greater susceptibility to COVID-19. In COPD, signs of endothelial cell dysfunction and tendency to thrombus formation have been identified which can present the risk of unfavorable outcomes of COVID-19. Cohort study data do not confirm that COPD patients are more susceptible to SARS-CoV-2 infection, but their clinical outcomes of COVID-19 appear to be worse including the need for mechanical ventilation and lethality. There is no clinical evidence about the role of inhaled glucocorticosteroids used to manage COPD in the development and course of COVID-19.